Enhancing mathematical learning of grade 4 students through active learning - Khammanee, Supakit; Prasertsang, Parichart; Matchimo, Puchong (Journal of Green Learning, 2023)
The objective of this research aims to develop mathematical learning activities through active learning management. The sample group used in this research consists of 23 students in grade 4. The research tools used include 15 lesson plans, a multiple-choice test with 20 items to measure learning performance, a multiple-choice test with 20 items to measure problem-solving abilities in mathematics, and a questionnaire to measure student satisfaction towards active learning management for mathematics subjects, consisting of 20 items. The statistical analysis used to analyze the data includes percentage, mean, standard deviation, and hypothesis testing. The research findings revealed that the active learning activities had an efficiency of 86.86/80.45. Students had learning score after the implementation is significantly higher than before, with statistical significance at the .05 level. The problem-solving abilities of students was higher than the criterion of 80%. Furthermore, students had level of satisfaction towards active learning management at the highest level.